Menggali Nilai-Nilai Islam Wasathiyah Dalam Kitab-Kitab Pesantren Sebagai Modalitas Mewujudkan Perdamaian Dunia - Ahmad Muzakki; Ahdiyat Agus Susila (HUMANISTIKA : Jurnal Keislaman, 2022)
Abstract This paper is intended to answer questions related to wasathiyah values, wasathiyah relations and peace, Islamic wasathiyah values ​​in Islamic boarding schools as a modality for pesantren in realizing world peace, and how to promote it as a solution for world peace. After conducting the analysis, it was concluded that moderation (wasathiyyah) is a characteristic of Islam which is a combination and unification of the concepts of ta'adul, tawazun and tawassuth in every pattern of thought, pattern of action, and behavior. At the practical level, the form of moderation in Islam can be classified into four areas of discussion, namely, moderate in matters of aqidah, moderate in matters of worship, moderate in matters of temperament and character, moderate in matters of the formation of the Shari'a. Promoting and campaigning for wasathiyah values ​​through pesantren education can prevent the emergence of radicalism in Indonesia and Muslim-majority countries in general. The promotion of wasathiyah Islam as strategic communication has an important role in maintaining Islamic education. Promoting wasathiyah in the context of Islamic boarding school education requires a balance between the process of delivering information and the process of self-transformation and the system. Knowledge sourced from the scientific tradition of Islamic boarding schools, when disseminated and interpreted in accordance with the wasathiyah concept, will eventually produce people who have strong faith, morality, moderation, and are able to understand and provide an understanding of Islam that is rahmatan lil `alamin.